PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA APRATUR SIPIL NEGARA PADA DISDUKCAPIL KABUPATEN HUMBANG HASUNDUTAN - Abdi Sugiarto; Ronita Panjaitan (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The majority of residents of Humbang Hasudutan Regency are farmers, whose routine is different from the ASN routine. Based on environmental culture, the perspective of motivation on employees and the comfort of the work environment is certainly different. Based on this phenomenon, this study aims to analyze the motivation and work environment on the performance of ASN in the Disdukcapil environment of Humbang Hasundutan Regency. This type of research is a causative research with a population of 65 people and with a saturated sampling method. Data analysis through several preliminary stages, classical assumption test, equation analysis, and hypothesis testing with t test and F test. Instruments with 24 questions to measure work motivation, work environment and employee performance have been declared valid and reliable. After going through statistical tests, it shows that motivation and work environment have a positive and significant effect on the performance of ASN Disdukcapil Humbang Hasundutan both simultaneously and partially. However, to optimize the performance of civil servants, it is necessary to explore other factors so that the performance of Disdukcapil Humbang Hasundutan Regency reaches a very good category. Adjustment of local culture also needs to be adjusted to the needs and habits of ASN Disdukcapil Humbang Hasundutan. Keywords: motivation, work environment, performance of civil servants, hasundutan, regression